2020
DOI: 10.47203/ijch.2020.v32i02.026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Activities of Daily Living (ADL) in elderly population

Abstract: Introduction: Most of the developing country facing growing number of elderly population because of decrease in fertility and increase in longevity. Elderly age (≥ 60 years) is a period in which people are prone to chronic diseases and their functional independency is probably restricted by physical and mental disabilities. Aim & Objectives: To find out the prevalence of physical dependency among elderly in Uttarakhand, India. Material & Methods: Activities of daily living (ADL) comprise the basic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…in Uttarakhand, 72.% of elderly participants were fully independent and 28% were dependent on others for their daily activities. [ 18 ] These findings are similar to our study. However, in a study by Chakraborty et al , in rural West Bengal, 18.8% of respondents were active; 45.6% of respondents were mildly disabled; 35.6% of respondents were severely disabled.…”
Section: Discussionsupporting
confidence: 93%
“…in Uttarakhand, 72.% of elderly participants were fully independent and 28% were dependent on others for their daily activities. [ 18 ] These findings are similar to our study. However, in a study by Chakraborty et al , in rural West Bengal, 18.8% of respondents were active; 45.6% of respondents were mildly disabled; 35.6% of respondents were severely disabled.…”
Section: Discussionsupporting
confidence: 93%
“…According to a study carried out in two randomly selected urban wards of Dibrugarh city, Assam, 34.7% of participants had limitations in one or more ADL items. [ 14 ] Another study, conducted by Usha et al ,[ 15 ] found that over a quarter of the elderly were dependent on others for their daily activities, with two-thirds having moderate to severe dependency. Another study conducted by Chauhan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on a study done by Usha et al where the total dependency rate was 28% was 81 with a 10% absolute error. 3 However, 200 participants were included in the study.…”
Section: Sample Sizementioning
confidence: 99%